Modulating effects of oral administration of Lycii Fructus extracts on UVB‑induced skin erythema: A Randomized, placebo‑controlled study. Issue 1 (2017) - TSUNENAGA, MAKOTO; XU, WENSI; ,; MYOJIN, TAKUMI; NAKAMURA, TOSHIYUKI; KON, TATSUYA; NAKAMURA, YOSHIMASA; UEDA, OSAMU
No abstract available